Soluble Block Copolyimides (Engineering of Polymers and Chemical Complexity, Volume II, 2014)
Abstracts ...100 5.1 Introduction ...100 5.2 Subject and Methods of Research ...100 5.3 Results and Discussion ...102 5.4 Conclusion ...104 Keywords ...104 References ...105ABSTRACT